The effect of POFA-gypsum binary mixture replacement on the performance of mechanical and microstructural properties enhancements of clays - Al-hokabi, Abdulmajeed; Muzamir, Hasan; Amran, Mugahed; Fediuk, Roman; Vatin, Nikolai Ivanovich; Alshaeer, Honin (MDPI AG, Basel, Switzerland, 2022)
Soft clay is categorized as problematic due to its weak and dispersive properties which requires stabilization. In Malaysia, there is another challenge, the increment of palm oil waste productions to meet the global demand for food oil. These two concerns motivate engineers to develop novel strategies for exploiting palm oil waste in soil stabilization. Utilizing POFA as a soil stabilizing agent is an economical and sustainable option due to that POFA contains high pozzolanic characteristics which make it more suitable and reliable to treat soft soil. This study uses the replacement portion of the soil with stabilizing agents -POFA and Gypsum; aiming to achieve Malaysia green technology goals by the balance of the economic expansion and environmental privilege. However, the aim of this study is to determine the effect of POFA-gypsum binary mixture replacement on the performance of mechanical and microstructural properties en-hancements of clays. Kaolin S300 is the control sample whereas POFA and gypsum are the used binders. The mechanical properties and shear strength with the curing period were tested. Results showed that treated clay marked increment of optimum water contents and reduction of maximum dry densities, a clear 200% of enhancement of treated clay’s compressive and shear strength with curing period as well as the amount of stabilizing agent to less than 15% of POFA and 6% of POFA. It is also found that as gypsum contains a high amount of lime (CaO), the results illustrate that strength raises significantly even with less curing time due to its high reactivity compared to silica and alu-mina. Overall, the results show an enhancement of mechanical and shear strength properties of treated kaolin supported by microstructural SEM imaging.